Laser treatment for genitourinary syndrome of menopause: Scientific Impact Paper No. 72 (July 2022). (27th July 2022) - Phillips, Christian; Hillard, Timothy; Salvatore, Stefano; Cardozo, Linda; Toozs‐Hobson, Philip; ,
Plain language summary: Genitourinary syndrome of menopause (GSM) is the term used to describe the group of symptoms including vaginal pain, vaginal dryness, itching, pain during sexual intercourse and fragile vaginal tissues as well as urinary symptoms including urinary frequency, urgency, incontinence, blood in the urine (haematuria) and recurrent urinary tract infections that occur due to a lack of the hormone estrogen. These symptoms can have a significant negative impact on psychosexual issues, sexual function and quality of life in postmenopausal women. Traditionally women have been treated with vaginal lubricants, vaginal moisturisers or low‐dose vaginal estrogens. Lasers have been used in the cosmetic industry for collagen remodelling and repair of the skin. Therefore, it has been suggested that laser therapy may be used on the vagina as an alternative treatment for GSM. A review of all the published studies assessing the safety and efficacy of laser therapy for GSM have shown promising beneficial results. The majority of studies to date have been small, short‐term, observational studies. However, there are randomised controlled trials underway. Laser treatment may be beneficial for the symptoms of GSM but until more robust evidence is available it should not be adopted into widespread practice, and should be used as part of a research study only.